2017
DOI: 10.1111/jcpp.12780
|View full text |Cite
|
Sign up to set email alerts
|

Very early hallucinatory experiences: a school‐based study

Abstract: Background The prevalence and clinical significance of hallucinatory experiences among children below 7 years of age remain unknown. We aimed to determine the independent influences of sensory deficits, the presence of an imaginary companion and metacognition on hallucinatory experiences. We assumed that hallucinatory experiences were associated with (a) sensory deficits, (b) the presence of an imaginary companion (IC) and (c) metacognition defaults (i.e. first‐ and second‐order theory of mind default). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…46,47 For example, Clemmensen et al 46 found paranoid delusions but not hallucinations to be associated with hyper-theory-of-mind. However, Pignon and colleagues 19 did find deficits in theory-of-mind skills in children with hallucinations. Perhaps the difference in age (and thus developmental stage) between these 2 studies can explain these different findings.…”
Section: Research Findings Since 2014mentioning
confidence: 94%
See 2 more Smart Citations
“…46,47 For example, Clemmensen et al 46 found paranoid delusions but not hallucinations to be associated with hyper-theory-of-mind. However, Pignon and colleagues 19 did find deficits in theory-of-mind skills in children with hallucinations. Perhaps the difference in age (and thus developmental stage) between these 2 studies can explain these different findings.…”
Section: Research Findings Since 2014mentioning
confidence: 94%
“…However, these measurements commonly assess the presence of hallucinations in the auditory domain only, using just a single item (eg “Have you ever heard voices or sounds that no one else can hear”). 19,29 Merely assessing the presence of hallucinations may be useful, but does not incorporate specific characteristics and qualities of hallucinations. For the purpose of this review, the focus will be on outlining (new) instruments specifically designed to assess the phenomenology of hallucinations in youth.…”
Section: Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…By age 3 he was experiencing intense, terrifying visual hallucinations of monkeys that caused him extreme distress. Childhood visual hallucinations of this quality and severity are an unusual symptom in younger children (Pignon et al, ). We found that the literature has not provided much detail regarding psychiatric symptomatology associated with trisomy 20.…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, some authors recently pointed out the value of more subtle phenomenological properties of hallucinations to decipher their mechanisms. 4 Despite the high occurrence of voices during development, even before 6 years of age, 5 the multisensory nature of experiences and their vividness were mentioned as particularly interesting properties in paediatric clinical populations. 6 The number of sensory modalities in hallucinations was even proposed as a proxy of the developmental vulnerability to hallucinations.…”
mentioning
confidence: 99%